Pathophysiological mechanisms, multidimensional diagnostics and modern therapies of pruritus in pancreatic cancer: review and perspectives - Włodyka, Jagienka Agata; Zelik, Urszula; Przygoda, Maria; Domino, Wiktoria; Trestka, Gabriela; Adamczyk, Sabina; Stępień, Kamila; Śnieżna, Joanna; Florczak, Wojciech; Dzwonnik, Karol; Dziewic, Jakub (Quality in Sport, 2025)
Introduction and purpose: Pruritus is a subjective, unpleasant sensation that leads to scratching and significantly impacts the quality of life of patients. In pancreatic cancer, its etiology is multifactorial. It can result from various mechanisms, with a particular emphasis on cholestasis, which represents the most important and frequent cause of this symptom, as well as paraneoplastic processes, neuropathic mechanisms, or side effects of therapy. The aim of this study is to analyze the mechanisms responsible for pruritus in pancreatic cancer, discuss diagnostic challenges, and review the available therapeutic methods and challenges, including bile duct decompression, the use of autotaxin inhibitors, opioid receptor antagonists, and SSRI drugs. The article is based on an analysis of the available scientific literature and cited sources. Description of the state knowledge: Topics discussed include pathomechanisms of pruritus in pancreatic cancer include cholestatic, opioid-induced, paraneoplastic, neuropathic and pruritus caused by antineoplastic therapies. Another key topic is the diagnostic process for pruritus in pancreatic cancer patients, which involves laboratory and imaging studies, clinical dermatological assessment, and differential diagnosis. Lastly, a comprehensive therapeutic approach is addressed, consisting of causal treatment, pharmacological interventions, and supportive care.